Implementation of Learning Models Numbered Head Together Through Tamansiswa Teachings Niteni, Niroke, Nambahi in the Written Indonesian Language Skills Course Elementary School Teacher Education Study Program - Siti Anafiah; Endang Hangestiningsih (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the implementation of the Numbered Head Together (NHT) learning model through the teaching of Niteni, Niroke, Nambahi (Tri N) teaching in the Indonesian Language Skills course in Writing at the PGSD Study Program at Sarjanawiyata Tamansiswa University in Yogyakarta. This type of research is qualitative research. The subject of research is S1 semester 3 students of PGSD FKIP UST. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using an interactive model. The analysis consists of three activities, namely: data reduction, data presentation, and drawing conclusions / verification. The results of this study were obtained that the application of the NHT learning model through the teaching concept of Tamansiswa Tri N in the KBIT course is contained in the Semester Learning Plan (RPS) and the learning process. In Niteni activities, students listened to the material explanation from the lecturer and intensively read the articles provided. Niroke, students working on assignments in groups to analyze the contents of the article with the formula 5W + 1H, the language and writing in accordance with the material that has been explained by the lecturer. Nambahi, one of the group representatives who had been appointed by the lecturer based on the number that was given to present the results of the discussion with the language and knowledge they have. Keywords: Numbered Head Together, Tri N, Write Indonesian Language Skills Abstrak Penelitian ini bertujuan untuk mendeskripsikan implementasi model pembelajaran Numbered Head Together (NHT) melalui ajaran tamansiswa Niteni, Niroke, Nambahi (Tri N) dalam mata kuliah Keterampilan Berbahasa Indonesia Tulis di Prodi PGSD Universitas Sarjanawiyata Tamansiswa Yogyakarta. Jenis penelitian ini adalah penelitian kualitatif. Subjek penelitian mahasiswa S1 semester 3 PGSD FKIP UST. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan model interaktif. Analisis tersebut terdiri atas tiga alur kegiatan, yaitu: reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian ini diperoleh bahwa penerapan model pembelajaran NHT melalui konsep ajaran Tamansiswa Tri N dalam mata kuliah KBIT terdapat dalam Rencana Pembelajaran Semester (RPS) dan proses pembelajarannya. Dalam kegiatan Niteni, mahasiswa menyimak penjelasan materi dari dosen dan membaca secara intensif artikel yang diberikan. Niroke, mahasiswa mengerjakan tugas secara berkelompok menganalisis isi artikel dengan rumus 5W+1H, bahasa dan tata tulisnya sesuai dengan materi yang sudah dijelaskan oleh dosen. Nambahi, salah satu perwakilan kelompok yang sudah ditunjuk oleh dosen berdasarkan nomor yang sudah diberikan untuk mempresentasikan hasil diskusi dengan bahasa dan pengetahuan yang dimilikinya. Kata kunci: Numbered Head Together, Tri N, Keterampian Berbahasa Indonesia Tulis